RE: Risk of HBV Reactivation in HBsAg Negative and AntiHBc IgG Positive Patients Receiving Biologic Therapy - Ergenç, İlkay; Kani, Haluk Tarık; Karabacak, Murat; Cömert Özer, Elif; Mehdiyev, Shahin; Jafarov, Fuad; Abacar, Kerem Yiğit; Kutluğ Ağaçkıran, Seda; Sevik, Gizem; Aslan, Rahmi; Alibaz Öner, Fatma; İnanç, Nevsun; et al. (Turkish Journal of Gastroenterology, 2023)
Cite this article as: Ergenç İ, Kani HT, Karabacak M, et al. RE: risk of HBV reactivation in HBsAg negative and anti-HBc IgG positive patients receiving biologic therapy. Turk J Gastroenterol. 2023;34(3):310.